Advances in propagation of Ficus carica L. - Boliani, Aparecida Conceição; Ferreira, Antonio Flávio Arruda; Monteiro, Laís Naiara Honorato; da Silva, Marcela Sant’Anna Cordeiro; Rombola, Adamo Domenico (FapUNIFESP (SciELO), 2019)
Fig tree (Ficus carica L.) stands out due to its range of cultivation and easy adaptation to diverse edaphoclimatic conditions. In addition to its adaptability, fruits have nutraceutical characteristics and are used in industry and for fresh consumption, widely appreciated by the world cuisine. Due to lack of manpower and phytosanitary problems, the area planted in Brazil has decreased recently. To overcome these obstacles, the production of quality seedlings is the first step to obtaining productive and healthy orchards. Therefore, the aim of the present literature review was to gather data referring to advances in research related to the fig tree propagation. Currently, the methods found for fig tree propagation consist of seedling production, where entomophilic or vegetative pollination occurs. Commercially, the propagation method by cutting is still the most used for this crop; however, other methods can also be used, such as the use of burrs or plunging and grafting techniques and tissue culture. Although there is a diversity of propagation methods and new technologies being developed, cuttings remain the most feasible method. In addition, obtaining healthy and quality seedlings is one of the main problems currently found in ficiculture, since, in addition to the scarcity of studies related to propagation, the use of resistant cultivars and pathogen-free substrates should be prioritized due to susceptibility of fig trees to nematodes. Thus, further studies should be carried out in order to seek new information on the cultivars most adapted to each locality, as well as improvements in propagation and cultivation techniques.
Avanços na propagação da Figueira
Keywords: Fig; Fruit tree; Pomology; Seedling production